Thyroid diseases - Hakimova Khonbuvi; Hakimova Khonbuvi; Sanakulova-Abdurasulova Gulchekhra Usmonovna (Peerian Journals Publishing, 2024)
This article analyzes the function of the thyroid gland, types of thyroid gland diseases, shows the causes of thyroid gland diseases, and briefly describes the methods of its treatment
Keywords: Thyroid gland; hypothyroidism; hormones; nervous system